Assessment of population structure and microsatellite based genetic variability in Sahiwal cattle - MUKESH, M; SODHI, M; MISHRA, B P; VIJ, P K; TANTIA, M S; BHATIA, S (The Indian Journal of Animal Sciences, 2014)
This study contributes to the knowledge of population structure; characterization and within breed genetic variability of Sahiwal cattle. Phenotypic characterization of Sahiwal cattle was carried out by conducting survey in its breeding tract to reveal its population structure, management practices, morphology and performance. Sahiwal herd performed reasonably well even under poor nutritional regime. Microsatellite genotyping at 25 loci revealed high within breed genetic variability in this milch breed of nor thern India.